Teach yourself DOS - Schikdt, Herbert (Berkeley, California : Osborne McGraw-Hill, 1990)
Covers MS-DOS and PC-DOS versions through 3.3 and 4.0, including computer basics, commands, directories, EDLIN, and other topics.
1. Learn computer basics -- 2. Run DOS for the first time -- 3. Learn some essential DOS commands -- 4. Master more DOS commands -- 5. Learn more DOS commands -- 6. Mastering directories -- 7. Master batch commands -- 8. Learn to redirect I/O -- 9. More DOS commands -- 10. Configuring DOS -- 11. Managing your system -- Appendixes.
Includes index.
Keywords: MS-DOS (COMPUTER FILE)